The Attitude to Artificial Intelligence its Relationship with future Orientation Among university students - Azeez Abbas, Riyadh (Al-Adab Journal, 2020)
Artificial intelligence it's the ability of a digital computer or computer-controlled robot to perform tasks commonly associated with intelligent beings or the branch of computer science dealing with simulation of intelligent behavior in computers.While, perceived rime distance of events forms another part of the psychological time, that is being affected by the physical distance of time as well as the orientation of the individual towards future and by the perceived value of activity and the importance of the event, it seems that the individuals look to themselves as if they are existing between the past and the future. The current research has targeted the following:The attitude to Artificial intelligence among university students.The future orientation among university students.Identifying the relationship between the attitude to artificial intelligence and future orientation among university students. The Results Was:University students characterized with attitude to artificial intelligence.University students characterized with future orientation.There is a statistically significant relationship between attitude to artificial intelligence and future orientation among university students.The researcher reached to several recommendations and suggestions